BUILDING INDONESIAN HUMAN CAPABILITY: REDUCING DEPENDENCY ON FOREIGN EXPERTISE IN THE FURTHER EDUCATION AND TRAINING SECTOR - Fairman, Brian; Voak, Adam; Maliki, (PEOPLE: International Journal of Social Sciences, 2020)
Foreign expertise holds a revered status in the Indonesian Further Education and Training sector, with the notion of ‘Bule’ playing a pivotal role in how international interventions are resourced. Foreign expertise often brings with it many local assumptions, particularly around the sharing of contemporary and start-of-the-art western knowledge, but often in reality this is not practically manifested. It is for these reasons that Maconick (1999) contends that greater emphasis needs to be placed on defining the operational role of local capacity building. The authors believe that greater emphasis should be placed on building local human capital, and this paper describes the engagement process in the design of occupational standards challenging the conception that foreign expertise and influence should be unfettered. While foreign skills and talent can play a pivotal role in developing local human capability, it must be recognised that these interventions must be cultural appropriate and look towards creating a sustainable future where indigenous human resources are given equal standing. The methodology applied reflected a ‘most significant change approach’ (Dart & Davies, 2003) to the evaluation of training methods with an emphasis on workplace engagement.